Prophylactic Effects of Astragalus Polysaccharides on Depression‐Like Behaviors in Rats With Chronic Unpredictable Mild Stress: A Role of Gut‐Microbiota–Brain Axis - Xiaojie Liu; Wenlu Xu; Ziyu Zhao; Xiaoling Wu; Senyan Wang; Chen Jian; Mengyu Li; Ke Li; Yulan Wang; Xuemei Qin (Food Frontiers)
ABSTRACT Radix Astragalus (RA) has been used in the treatment of depression. Astragalus polysaccharide (APS) is one of the effective components of RA. However, the antidepressant mechanism of APS is still unclear. This research utilized 16S rRNA analysis, microbial analysis, and metabolomics analysis to elucidate the antidepressant mechanism of APS at both micro and macro levels. Correlation analysis was performed on the perspective of “behavioral indicators‐intestinal bacteria‐immune factors‐differential metabolites” to show the relationships among various indicators. The results showed that APS could significantly regulate the depressive behaviors of depressed rats, alleviate the imbalance of Th17/Treg, increase the expression level of anti‐inflammatory factor IL‐10, while reduce the expression level of pro‐inflammatory factor IL‐22. APS significantly reduced the expression levels of lysine, alanine, and arginine of depressed rats, as well as the abundance of Aerococcus. Lysine and arginine were the most closely related to behaviors, immune factors, and gut bacteria. The current findings revealed the antidepressant mechanism of APS from the perspective of the “gut microbiome–immunity–metabolome” axis. This study provides a new strategy for proving the antidepressant effects of plant polysaccharides and lays a solid foundation for the discovery of new drugs from botanical drugs and the improvement of patients' quality of life.